Hubungan Pola Konsumsi Islamic-Themed Fast Food Dengan Physical Health Pada Remaja di SMPN 2 Pariaman - Andriani, Linda; Ratih, Septiana; Maersela, Putri Diana (Eshraq: Journal of Islamic Studies, 2026)
Adolescents represent an age group undergoing a transitional phase toward adulthood, characterized by rapid physical growth, hormonal changes, and complex psychosocial development. Amid globalization and modernization, adolescent dietary patterns have shifted from nutritious traditional foods to fast food, which is practical but low in nutritional value. This phenomenon is increasingly prevalent among urban adolescents, including those in Pariaman City. This study aims to determine the relationship between fast food consumption patterns and physical health among adolescents at SMPN 2 Kota Pariaman. This research employed a quantitative method with a descriptive correlational approach and a cross-sectional design. The study was conducted from July 21 to 25, 2025, involving 80 students from grades VIII and IX, selected through stratified random sampling. Data were collected using a Food Frequency Questionnaire (FFQ), a Likert scale to assess physical health complaints, and Body Mass Index (BMI) measurements. Data analysis was performed using the Chi-Square test. The results showed a significant relationship between fast food consumption and physical health (p-value = 0.024 < α = 0.05). A total of 45% of respondents were categorized as “frequent” consumers and 23.8% as “very frequent.” Regarding physical health, 41.3% experienced moderate complaints, 33.8% severe complaints, and 25% mild complaints. Notably, 57.9% of adolescents who consumed fast food very frequently reported severe physical health issues, while those who rarely consumed fast food mostly reported mild complaints (36%). It can be concluded that fast food consumption patterns are significantly associated with physical health among adolescents. Therefore, it is important for adolescents to maintain healthy eating habits to avoid the negative impacts of fast food on their physical well-being.